Design of a Low Cost Biomedical Parameter Monitoring System - Parate, R. K.; Sharma, S. J. (Novel Perspectives of Engineering Research Vol. 4, 2021)
In the present work, we have designed a biomedical parameter monitoring system using Node MCU to monitor body temperature, heart rate and oxygen saturation level (SpO2) signals. These signals are sensed by respective sensors. In our laboratory, we designed the necessary signal conditioning circuits using off-the-shelf electronic components. ESP 32 Node MCU based data acquisition system has been designed for acquisition of respective biomedical parameters. The developed prototype is the cost effective solution to the commercially available biomedical parameters monitoring systems. Necessary processing code is developed using C language in Arduino IDE and uploaded into the Node MCU. All the acquired parameters have been displayed on OLED display module. The developed system has been tested on 50 subjects of different age group and sex. Error analysis has been done on obtained results. The developed prototype shows that accuracy of the system for measured parameters is 98%. The designed system provides portability, high functionality and low cost which makes it an easy accessible tool for common man, clinical environment and other medical purposes.